Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.3324/haematol.12515
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of maternal anti-HPA 1a antibody level as a potential predictor of alloimmune thrombocytopenia in the newborn

Abstract: BackgroundNeonatal alloimmune thrombocytopenia is most commonly due to transplacental passage of maternal anti-HPA 1a antibodies. A prospective study was carried out to evaluate the pattern and quantity of maternal anti-HPA 1a antibodies in order to predict the level of thrombocytopenia in the neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 26 publications
(38 reference statements)
4
122
0
4
Order By: Relevance
“…Thus, several other factors are playing a role to modulate incidence and severity of the disease. In humans, a correlation between HPA1a Ab titers in the mother and severity of the thrombocytopenia at birth has been reported, despite several analytical variation factors (35)(36)(37). FcRn, the neonatal IgG receptor, has been shown to modulate FNAIT in a mouse model (38).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several other factors are playing a role to modulate incidence and severity of the disease. In humans, a correlation between HPA1a Ab titers in the mother and severity of the thrombocytopenia at birth has been reported, despite several analytical variation factors (35)(36)(37). FcRn, the neonatal IgG receptor, has been shown to modulate FNAIT in a mouse model (38).…”
Section: Discussionmentioning
confidence: 99%
“…Immunization against HPA-1a occurs in ;1:450 random pregnancies. [8][9][10] Although platelet decrement is related to antibody titer in FNAIT, 8,11,12 this correlation is not strict, as cases with low titers and very low platelet counts, as well as cases with high titers and normal platelet counts, are frequently observed. Recently we found that at least some of this discrepancy is due to differences in the functional quality of these antibodies, determined by its Fc glycosylation, in particular the level of core fucosylation.…”
Section: Introductionmentioning
confidence: 99%
“…Det kliniske forløpet ved føtal/neonatal alloimmun trombocytopeni er svaert varierende og spenner fra lett redusert trombocyttall med spontan normalisering til alvorlig trombocytopeni med intrakranial blød-ning og neonatal død. I flere studier er det vist sammenheng mellom antistoffnivået hos moren og trombocyttallet hos barnet (7,9). I tillegg er det vist at behandling av moren før fødselen med intravenøs injeksjon av polyklonalt immunglobulin og steroider reduserer forekomsten av hjerneblød-ninger (9,10).…”
Section: Figur 1 Mr Caput T2-opptak Med 15 Tesla-maskin Bildeopptaunclassified
“…Kvinnen vil ha normalt trombocyttall og kan immuniseres i første svangerskap (25 %) eller i forbindelse med forløsningen (75 %). Dermed kan fosteret vaere affisert i første svangerskap (7). Dette står i kontrast til antistoffmediert hemolytisk sykdom hos nyfødte, der problemet sjelden oppstår i første svangerskap, men oftest i påfølgende uforlikelige svangerskap etter immunisering.…”
unclassified